2014
DOI: 10.1542/peds.2013-1505
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Viral Gastrointestinal Infection: The Missing Link?

Abstract: We present the case of an 8-month-old boy who presented with apparent life-threatening events later characterized as seizures in clusters. A total of 14 apneic episodes were observed within 24 hours before loading the patient with phenobarbital at which point the seizures stopped. There was no obvious explanation for his seizures. EEG revealed midline interictal discharges; MRI-head was normal; and all other investigations were normal. The patient' s stool was sent for virology with the clinical suspicion of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…While a key principle of PCMH is that team-based care can promote greater levels of patient engagement, one large study showed that only about one-quarter of practices with PCMH recognition included pharmacists, social workers, community service coordinators, and nutritionists on their care teams. 17…”
Section: Expanded Staffingmentioning
confidence: 99%
See 4 more Smart Citations
“…While a key principle of PCMH is that team-based care can promote greater levels of patient engagement, one large study showed that only about one-quarter of practices with PCMH recognition included pharmacists, social workers, community service coordinators, and nutritionists on their care teams. 17…”
Section: Expanded Staffingmentioning
confidence: 99%
“…19 Some practices make a concerted effort to register patients on the practice's portal. 20 MAPCP providers often view their portals as time-saving and useful for interacting with patients, and patients also tend to value them.…”
Section: Improving Access and Continuitymentioning
confidence: 99%
See 3 more Smart Citations